Analisis Biaya-Volume-Laba untuk Perencanaan Laba Operasi - Gani, Engelwati (Binus Business Review, 2013)
This study conducted cost-volume-profit analysis of the company. A maximum profit can be obtained by analyzing sales volume and product mix to be sold. So that, the cost-volume-profit analysis can be used as a planning strategy of the companyâs operations profit. To do so, semivariable costs must be separated into variable and static costs. After that the breakeven point can be calculated. By knowing the breakeven point, operations profit planning expected can be made. Research used qualitative method with direct contact by interviewing the company and indirect contact by observing the companyâs profit-loss financial statements from 2008 to 2011. PT SD Textile is a manufacturing company engaged in the manufacture of damask, sheet and towel. Conditions of sales and the cost of sales have increased in the period of 2008 to 2010 and have decreased in the period of 2011; while the operations expenses have increased in the period 2008 to 2011. The increase and decrease in sales, the cost of sales and operations expenses have a direct impact on the operations profit. The operations profit increased in the period of 2008 to 2009 and decreased in the period of 2010 and increased again during the period of 2011. Given the situasion, it is very important for PT SD Textile to do operations profit planning with attention to sales planning and costs in order to deliver the maximum profit.